Pengaruh pelapisan benih dengan Polyethylene glycol (PEG) dan lama penyimpanan terhadap viabilitas benih tomat ceri (Solanum lycopersicum var. cerasiforme) - Velly Dontor Nahampun; Florentina Kusmiyati; Budi Adi Kristanto (Journal of Agro Complex, 2018)
The research aimed to study the effectiveness of polyethylene glycol (PEG) as seed coating to maintain viability of cherry tomato during different storage period. This research was conducted in June to October 2017 at Laboratory of Plant Physiology and Breeding, Faculty of Animal and Agricultural Sciences, Diponegoro University. The research was assigned in completely randomized factorial design with the first factor was the level of PEG (0%, 20%, 40%, and 60%) and the second factor was the storage period (30 days, 60 days, and 90 days). Parameter were percentage of germination seed, seed water content, and dry weight of normal seedling. The data were analyzed using analysis of variance and continued by Duncan Multiple Range Test. The result showed that there was interaction between seed coating and storage period that affected percentage of germination seed, seed water content, and dry weight of normal seedling. Seed coating with PEG 20% and 90 days storage was able to maintain the percentage of germination up to 97.2%, seed water content of 7.39 % and dry weight of normal seedling of 0.66 g. Keywords : Percentage of germination, seed water content, dry weight of normal seedling